Removal of methyl red in wastewater by activated carbon derived from rice husk (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
The textile industry is the largest industry contributing to the wastewater pollution and is a concern for the environment today. This pollution occurs when wastewater from the textile industry discharges the water into the river and it will affect both aquatic and human life. There are several ways to overcome this pollution problem but the current method is very expensive and its effectiveness depends on the colour of the dye. In this research, activated carbon of rice husk was used as an adsorbent to remove the methyl red dye from the wastewater. To detect the effectiveness of rice husk, two materials were used which were raw rice husk and also activated carbon to remove methyl red dyes from wastewater. There are four parameters used to investigate the optimum level which are the effect of initial dye concentrations ranges from (2 mg/L-10 mg/L), contact time (20-100 minutes), pH (2-10) and adsorbent dosage (0.5-2.5 g). The percentage of dye is calculated and recorded to see the comparison between raw rice husk and also activated carbon of rice husk. The results show that the rice husk can be used as a potential adsorbent to remove methyl red from the waste water.
Keywords: rice husk; methyl red dye; activated carbon